2011
DOI: 10.1093/jscr/2011.8.9
|View full text |Cite
|
Sign up to set email alerts
|

Giant urethral calculus

Abstract: Primary urethral calculus is rarely seen and is usually encountered in men with urethral stricture or diverticulum. We present a case of giant urethral calculus secondary to a urethral stricture in a man. The patient was treated with calculus extraction with end to end urethroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 1 publication
0
13
0
Order By: Relevance
“…True prostatic calculi are formed by the deposition of calcareous material on the corpora amylacea [2,3]. Prostatic urethral stones are classified as endogenous or primary (those formed de novo in the urethra) and exogenous or secondary (those formed in the upper urinary tract with secondary downward descent) [4,5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…True prostatic calculi are formed by the deposition of calcareous material on the corpora amylacea [2,3]. Prostatic urethral stones are classified as endogenous or primary (those formed de novo in the urethra) and exogenous or secondary (those formed in the upper urinary tract with secondary downward descent) [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…They are magnesium ammonium phosphate (struvite), calcium phosphate or calcium carbonate in composition, have no nucleus and are of uniform structure. They are formed in the urethra proximal to strictures, in congenital and acquired diverticula, with chronic infection with especially urea splitting organisms or with foreign bodies [5]. They generally do not cause acute symptoms because of their slow development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Formation of Pt nanoparticles on montmorillonite surface was carried out by hydrogen reduction of tetraamine Pt-complex intercalated into montmorillonite at 140 o C (201). Kotkar et al (202) reported the synthesis of Rh nanoparticles in the interlayer of montmorillonite by oxidative degradation of intercalated tris(phenanthroline)-Rh(III) composite followed by reduction under hydrogen atmosphere. Pt onanoparticle stabilized on montmorillonite was prepared (203) …”
Section: Reduction With Hydrogenmentioning
confidence: 99%
“…Manikandan temperature and a moderate pressure of hydrogen, efficient hydrogenation of cinnamaldehyde giving rise to cinnamyl alcohol in high yield using low loaded Pt-nanoparticles in the interlayer of montmorillonite. Thakkar et al (202) reported the hydrogenation of cycloalkane using Rh nanoparticle supported montmorillonite. Pd-nanoparticles immobilized in an organo-montmorillonite was catalytically effective towards the hydrogenation of various olefins as reported by Kiraly et al (225).…”
Section: Hydrogenationmentioning
confidence: 99%